INSTAGRAM SEBAGAI MEDIA EKSPRESI HASRAT SEKSUAL PEREMPUAN - Widya Hapsari, Arinta; Lukmantoro, Triyono; Hasfi, Nurul (Interaksi Online, 2024)
This research discusses the social media Instagram as a medium for women to express their sexual desires. The aim of this research is to describe and understand the experiences of women who express their sexual desires on Instagram. This type of research is descriptive qualitative and the method used in this research is in-depth interviews with informants.The results of research from in-depth interviews with informants show that when they first expressed their sexual desires they felt attracted to, curious about Prince Abdul Mateen and the influence of the surrounding environment. Women still hide behind anonymous accounts and are brave because fellow women have the same thoughts. This is not in line with the Existentialist Feminism Theory put forward by Simone de Beauvoir. The impact is that they only get satisfaction in expressing their opinions and expressing their sexual desires, giving appreciation to Prince Abdul Mateen. Apart from that, the response given by the informants regarding the news circulating on the internet was an attitude of ignorance and only following the response of the individual who was the 'object'. While the space provided by Instagram has provided satisfactory expression and adequate features, although some still feel that there are restrictions on expression on Instagram.